Emerging Technologies for Green Energy Conversion and Storage. (15th February 2021) - Zhang, Qian; Suresh, Lakshmi; Liang, Qijie; Zhang, Yaoxin; Yang, Lin; Paul, Nikita; Tan, Swee Ching
Abstract: The biggest concern of the decade is to find a way to power the future in the most ecofriendly and green manner, owing to current energy crisis and environmental pollution. A major side effect of conventional technological advancements is the inability to naturally digest and decompose the substances human society has created. This review summarizes green energy conversion and storage devices with a particular focus on recent advancements in emerging technologies. Technical innovations in energy‐related materials, device structures, and new applications are discussed. Furthermore, hybrid energy and self‐charging power systems are discussed in conjunction with recent and future research directions. The multifunctional applications of these energy systems are also emphasized. It is expected that this review will provide a platform to understand the current landmarks and promote further research to broaden the utility of energy devices. Abstract : This review presents recent progress on emerging methods for green energy conversion, storage, and power systems. A broad spectrum from advisable materials, novel device designs to performance optimization even in harsh environments is covered. Multifunctional utilization of some existing energy technologies is discussed to solve real life problems. This review is anticipated to be of great importance for the design and improvement of future energy technologies.